Composite cellulose/bismuth/PVA nanocrystal for high-performance X-ray radiation shielding - Ihsani, Rifqah Nurul; Alomari, Ali Hamed; Gareso, Paulus Lobo; Heryanto, Heryanto; Ardiansyah, Ardiansyah; Abdul Karim, Muhammad Khalis; Tahir, Dahlang (Elsevier Ltd, 2025)
The strong penetrating power of X-rays causes serious health problems. Longer exposure to radiation that penetrates normal cells can result in gene mutations, cancer, and even death. Protection against radiation exposure is necessary to prevent negative impacts from occurring. This research aims to make apron samples using a simple method based on cellulose as a matrix, bismuth as a filler with concentrations of 1 g, 0.75 g, 0.25 g and PVA acts as a binder that helps bind cellulose and bismuth particles into an effective X-ray radiation shield. The characterization carried out includes Fourier transform infrared (FTIR) to determine the functional groups and chemical composition of the sample, x-ray diffraction (XRD) to analyze the crystal size of the sample, and mobile x-ray with energies of 60, 70, and 80 keV to determine the radiation shielding performance. The findings of this study highlight that the optimal shielding properties were attained by employing a sample with the highest concentration of bismuth filler, specifically at 1 g. This material exhibits outstanding characteristics, including a high linear attenuation coefficient and mass attenuation coefficient of 0.68 cm−1 and 2.24 cm2/g respectively for an energy of 60 keV and especially low HVL (1.01 cm) and TVL (3.36 cm) values. These findings have significant implications for developing high-performance X-ray radiation shielding materials, particularly in industries where radiation exposure is a concern, such as the medical industry, research, and laboratories. The high tensile strength (2.83 N/mm2) and elongation (12.09 %) values as well as the low Young's modulus (0.108 N/mm2) values also indicate the flexibility of the resulting material, which could be beneficial for applications that require flexible shielding materials. The practicality of this research makes the audience feel that the findings are applicable and useful in real-world scenarios.